In Porphyromonas gingivalis VimF Is Involved in Gingipain Maturation through the Transfer of Galactose - Muthiah, Arun S. (Public Library of Science, 2013)
Previously, we have reported that gingipain activity in Porphyromonas gingivalis, the major causative agent in adult periodontitis, is post-translationally regulated by the unique Vim proteins including VimF, a putative glycosyltransferase. To further characterize VimF, an isogenic mutant defective in this gene in a different P. gingivalis genetic background was evaluated. In addition, the recombinant VimF protein was used to further confirm its glycosyltransferase function. The vimF-defective mutant (FLL476) in the P. gingivalis ATCC 33277 genetic background showed a phenotype similar to that of the vimF-defective mutant (FLL95) in the P. gingivalis W83 genetic background. While hemagglutination was not detected and autoaggregation was reduced, biofilm formation was increased in FLL476. HeLa cells incubated with P. gingivalis FLL95 and FLL476 showed a 45% decrease in their invasive capacity. Antibodies raised against the recombinant VimF protein in E. coli immunoreacted only with the deglycosylated native VimF protein from P. gingivalis. In vitro glycosyltransferase activity for rVimF was observed using UDP-galactose and N-acetylglucosamine as donor and acceptor substrates, respectively. In the presence of rVimF and UDP-galactose, a 60 kDa protein from the extracellular fraction of FLL95 which was identified by mass spectrometry as Rgp gingipain, immunoreacted with the glycan specific mAb 1B5 antibody. Taken together, these results suggest the VimF glycoprotein is a galactosyltransferase that may be specific for gingipain glycosylation. Moreover, galatose is vital for the growing glycan chain.